2009
DOI: 10.23938/assn.0437
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive factors in early breast cancer

Abstract: RESUMENSon muchos los factores pronósticos y predictivos potenciales en el cáncer de mama y su número aumenta continuamente. Las aportaciones a este incremento de las nuevas tecnologías para el estudio de los materiales genéticos, capaces de medir miles de genes simultáneamente en un único espécimen tumoral, son fundamentales; aunque su incorporación a la práctica clínica dependerá del adecuado diseño y análisis de las investigaciones.Sin embargo, los factores pronósticos validados son pocos y no han aumentado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It implement the genetic algorithm using Galgo [ 23 ]. This software is an object-oriented programming (OOP) implementation in R. Further, it includes the code to develop models using Random Forest [ 28 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It implement the genetic algorithm using Galgo [ 23 ]. This software is an object-oriented programming (OOP) implementation in R. Further, it includes the code to develop models using Random Forest [ 28 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other research, which is based on texture description, spectral clustering, and Support Vector Machine (SVM) for the detection of breast masses [ 27 ], also aims to obtain more informative features. Other multivariate analysis approaches have demonstrated that prognostic information and predictive factors can be obtained to identify breast cancer in its early stages [ 28 ]. Among the different techniques of digital image processing and pattern recognition that have been applied in breast cancer, the use of mutual information and a greedy selection are used for this diagnosis when the information is uniformly distributed [ 29 ].…”
Section: Introductionmentioning
confidence: 99%